Detection of tilapia lake virus (TiLV) by seminested RT-PCR in farmed tilapias from two regions of Peru - Castañeda Vargas, Arnaldo Edward (2020)
The production of tilapia (Oreochromis sp) is being affected by outbreaks of lake tilapia virus (TiLV) with high mortality in the main breeding regions in Peru. The aim of this study was to determine the presence of TiLV in two tilapia fish farms in Piura and San Martín, which presented mortalities greater than 60%. Samples (liver and brain) were taken from 70 fish from different stages of culture that showed lethargy, loss of appetite, eye lesions and skin erosions. The detection and confirmation of TiLV was determined by semi-nested RT-PCR and subsequent sequencing of the amplified product of segment 3 of the virus. Products of the expected weight (250 bp) corresponding to samples from the two production centres were found. The phylogenetic analysis showed a high homology among the isolates and an identity greater than 90% with the Israeli reference strain (KU751816.1).